Introduction: The Peace Agreement between the Colombian government and the FARC-EP, or the elusive peace - Farid Samir Benavides (Revista CIDOB d'Afers Internacionals, 2019)
The Peace Agreement or Final Agreement between the Colombian government and the FARC-EP brought the armed conflict with the guerrilla organisation to an end. The agreement is seen as a model due to several of its features: among others, its gender and ethnic perspective, and its methodology of negotiation in the midst of conflict. This introductory article seeks to present the background to the peace process and the main lines of the agreement reached. It also makes a preliminary assessment of compliance with the accords (as of April 2019) and the prospects of success. A general context is thereby provided to the papers included in this issue of Revista CIDOB d’Afers Internacionals, which is dedicated to the peace process in Colombia, and to understanding the framework within which its contents should be interpreted.